The role of USP36 in ribosome biogenesis and other pathophysiological processes - Shao, Linxin; Guo, Mengqi; Kou, Qianrui; Guo, Ya; Li, Xin; Li, Fang (Frontiers in Molecular Biosciences, 2025)
Ubiquitination and deubiquitination are common forms of protein post-translational modifications that play crucial roles in the regulation of intracellular homeostasis. As a member of deubiquitination enzyme USP family, USP36 maintains the stability of substrate proteins by mediating their deubiquitination, thereby playing a significant role in various pathophysiological processes. Here we focus on discussing how USP36 participates in regulating ribosome biosynthesis and responds to ribotoxic stress response. Furthermore, this review has elucidated the role of USP36 in regulating DNA replication stress, hypoxia adaptation, oxidative stress, and selective autophagy, as well as the related molecular mechanisms. This review is very helpful for understanding the role of USP36 in pathophysiological process and exploring the possibility of USP36 as a target for disease treatment.